Structural Analysis of the AlkB Family in Poultry - Niu, Yuling; Li, Kan; You, Xuerong; Wu, Yutao; Du, Xue; Zhao, Ayong; Wang, Zhijun (Animals (Basel), 2025)
The objective of this study was to identify the AlkB family genes in poultry using bioinformatics, and to explore their molecular characteristics, evolutionary relationships, and expression patterns to clarify their potential functions in poultry. (1) Methods: The study utilized the NCBI database to obtain chicken genome data, and screened and validated AlkB family members (ALKBH1-5, ALKBH8, and FTO) by hmmsearch and TBtools. MEGA 11.0 was used for phylogenetic analysis, PHYRE2 and I-TASSER predicted protein structures, and the String database was used to construct an interoperability network. Finally, the tissue expression profiles were analyzed by using The Human Protein Atlas online database and qRT-PCR. (2) Results: Phylogenetic analysis revealed distinct avian and mammalian clusters, with chicken AlkB proteins exhibiting low sequence homology but conserved 3D structures compared to mammals. Chromosomal synteny and conserved domains highlighted evolutionary divergence, with ALKBH4 lacking typical AlkB structural motifs. Protein interaction networks linked ALKBH1/2/3/5/8/FTO, underscoring functional coordination in poultry adaptation. Tissue-specific expression showed high AlkB levels in brain tissues, while ALKBH5 dominated in muscle. During differentiation, ALKBH3, ALKBH5, and FTO expression significantly increased during myoblast differentiation. (3) Conclusions: This study identified seven AlkB family genes in poultry, revealing their phylogenetic classification into two subfamilies, conserved structural domains, chromosomal synteny, and tissue-specific expression patterns.